The Evolution of Equid Monodactyly: A Review Including a New Hypothesis - Janis, Christine M.; Bernor, Raymond L. (Frontiers in Ecology and Evolution, 2019)
The traditional story of horse evolution is well known: over time, horses became larger, they attained higher-crowned teeth, and they changed from having three toes (tridactyly) to a single toe (monodactyly). Evolution is often perceived as a progression towards some optimum outcome, in this case the “Noble Steed.” However, the evolutionary advantages of monodactyly are not entirely clear, other than the notion that it must somehow be “more efficient,” especially at the larger body size of the genus Equus. It is not commonly appreciated that the reduction of the digits to the monodactyl condition was not the main anatomical foot transition in equid history. Rather, the most important change was the transformation of the original “pad foot” into the more derived “spring foot,” with the acquisition of an unguligrade limb posture, characteristic of the family Equinae. Species within the Equinae tribes – Hipparionini, Protohippini, and Equini – evolved hypsodont teeth and diverged into both small and large body sizes, but monodactyly evolved only within the Equini. Despite the Plio-Pleistocene success of Equus, Hipparionini was by far the richest tribe for most of the Neogene, in terms of taxonomic diversity, numbers of individuals, and biogeographic distribution; but hipparionins remained persistently tridactyl over their duration (17-1 Ma). We propose that the adaptive reasons for monodactyly must be considered in the context of reasons why this morphology never evolved in the Hipparionini. Additionally, Equus inherited monodactyly from smaller species of Equini, and consideration of Miocene taxa such as Pliohippus is critical for any evolutionary hypothesis about the origins of monodactyly. We review the literature on equid locomotor biomechanics and evolution, and propose two novel hypotheses. (1) The foot morphology of derived Equini is primarily an adaptation for increasing locomotor efficiency via elastic energy storage, and the accompanying digit reduction may be circumstantial rather than adaptive. (2) Differences in foraging behavior and locomotor gait selection in Equini during late Miocene climatic change may have been a prime reason for the evolution of monodactyl horses from tridactyl ones.